Creative Responsiveness, Dramatic Performance, and Becoming-Democratic. Issue 2 (May 2019) - Goktepe, Katherine
Abstract : This article draws upon work by Gilles Deleuze, Sanford Meisner, and William Connolly to argue that the practice of acting helps citizens to encounter unsettling circumstances in daily life; respond to and connect with others in more open, interactive ways; and expand the relatively stable repertoire of selves each person cultivates through life. Considering scenes from the films of Anna Magnani, Ronald Reagan, and Joan Crawford, I argue that acting spaces can be sites where an exploration and decentring of subjectivity can proceed and new modes of democratic interaction and togetherness can be enacted.